Policy Implementation of Poverty Countermeasure Through Independent Urban ‘PNPM’ (President Rule Study Number 15 Year 2010 about Acceleration of Poverty Countermeasure in Malang City) - Nurul Nurul; Abdul Juli Andi Gani; Bambang Santoso Haryono (Sekolah Pascasarjana Universitas Brawijaya, 2017)
National Program for Community Empowerment (PNPM Mandiri MP) is a government program in accelerating the poverty reduction through community empowerment approach. According to Presidential Regulation No. 15/2010, the National policy strategy of poverty reduction is an attempt conducted by government to tackle poverty. The implementation of community empowerment through PNPM-Urban Mandiri programs involved all stakeholders and policy makers among government, community and others. This study aimed to describe and analyze the process of communication, resources, commitment and bureaucratic structure as well as supporting and hindering factors of PNPM-Urban Mandiri implementation. The research method used in this study was qualitative and it was taken in PNPM-Urban Mandiri Kota Malang , East Java Province. The data analysis used was interactive data analyzing models. The result of the study shows that the implementation of PNPM-Urban that the policy of poverty reduction conducted based on the Presidential Regulation No. 15/2010 has still not effectively implemented as well as found some obstacles and problems that caused the objectives has not achieved. They were influenced by communication, resources, commitment, and bureaucratic structures.